Modes of action of the protective strain Fo47 in controlling verticillium wilt of pepper. (23rd November 2015) - Veloso, J.; Alabouvette, C.; Olivain, C.; Flors, V.; Pastor, V.; García, T.; Díaz, J.
Abstract : The protective fungus Fusarium oxysporum Fo47 reduces the severity of wilt caused by the soilborne pathogen Verticillium dahliae in pepper. Modes of action responsible for the biocontrol activity were studied. Microscopic observations of fluorescent protein‐transformed strains colonizing the root surface show that the colonization patterns of Fo47 and V. dahliae were similar. Pixel counting of the images obtained by confocal microscopy showed that Fo47 reduces colonization of the root surface by V. dahliae, suggesting a possible role of competition for nutrients at the root surface. Besides these effects on surface colonization, the hormonal pathways activated during priming of plant defence responses were identified by measuring the amount of some phytohormones and their derivatives in roots and stems of pepper. Results showed an early, slight increase of jasmonyl isoleucine, followed by a transient increase of salicylic acid during the pre‐challenged phase of priming and an increase of 12‐oxo‐phytodienoic acid during the challenge phase of priming. The caffeic, ferulic and chlorogenic acids, known to play a role in plant defence reactions, showed a strong antimicrobial activity against V. dahliae in vitro . In pepper roots, Fo47 stimulated the biosynthesis of caffeic acid and primed that of chlorogenic acid. These results demonstrated that the effective control of V. dahliae provided by Fo47 is based on different but complementary mechanisms.